Nomad : From Islam to America :A Personal Journey Through the Clash of Civilizations - Hirsi Ali, Ayaan, 1969- (New York Free Press, 2011)
Describes the author's experiences after moving to America to pursue a safer life, from her renewed contact with her family after her father's death to her struggles to embrace new principles in the face of attempts to prohibit her work.
Keywords: Women social reformers -- United States -- Hirsi Ali, Ayaan, 1969-